The Pro12Ala polymorphism of the gene for peroxisome proliferator activated receptor‐gamma is associated with a lower Global Acne Grading System score in patients with acne vulgaris. (1st July 2014) - Amr, K.; Abdel‐Hameed, M.; Sayed, K.; Nour‐Edin, F.; Abdel Hay, R.
Summary Background Acne vulgaris is a multifactorial disease of the skin. Several studies have shown that sebocyte proliferation and/or lipogenesis, as well as inflammatory reactions, may be regulated by peroxisome proliferator‐activated receptor (PPAR)γ‐mediated pathways. Aim To investigate whether the Pro12Ala polymorphism of the PPARγ gene might be associated with the risk of acne, and to assess the effect of this polymorphism on acne severity. Methods This case–control study enrolled 100 patients with acne and 100 apparently healthy subjects. The clinical grade of acne was assessed using the Global Acne Grading System. We used PCR to identify the presence of the Pro12Ala polymorphism in exon 2 of PPARγ. Results Our results revealed a statistically significant difference (P = 0.001) in the genotype distribution between patients and controls, with higher incidence of the Pro/Ala genotype in controls (51%) than in patients (28%). A statistically significant association (P < 0.001) between disease severity and genotype distribution was found, indicating that the Pro/Ala genotype is less prevalent in patients with severe acne. Conclusions Our results suggest that that the Ala allele might be a protective factor against acne development or may attenuate acne severity.